Gambling disorder: an overview - Çakmak, Soner; Tamam, Lut (Journal of Dependence, 2018)
Psychopathologically, the concept of addiction in the terminology of psychiatry has gained a different perspective as a result of behavioral research under the influence of behavioral approaches. Neuroimaging, processing of neurobiological data has contributed to this change in the last 10 years, as the data on comorbidity, inheritance, tolerance, withdrawal symptoms and treatment outcomes among addictions show similarities. Gambling addiction was also affected by this change and new perspectives on the etiology, diagnostic criteria and treatment were developed. With the recently published Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), gambling addiction was included in the category of addictions and under the heading "Non-substance related disorder" in the category "Drug Related and Addictive Disorders". This new point of view is likely to be gambling addiction, perhaps leading to the fact that behavioral addictions such as internet use, playing video games, eating and shopping can be evaluated within the context of addiction, and will develop a new perspective on behavioral addictions. The aim of this article is to review gambling disorder within the axis of DSM-5 and assess it from the viewpoint of diagnosis, epidemiology, etiology, comorbidity and treatment.
Keywords: gambling; addiction; diagnosis; comorbidity; treatment